Comparison of experimental charring rate of some selected constructional wood species from south western Nigeria with selected charring models. - Adetayo, O. A.; Dahunsi, B. I. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The rate at which timber chars varies between species and predominately dependent on density and moisture content. This study involved determination of charring performance of Nigerian wood species used for constructional purposes and comparing their charring rate with selected existing models. Six out of ten identified wood species commonly used for constructional purposes: Terminalia superba (Black Afara), Milicia excels (Iroko), Nauclea diderrichii (Opepe), Khaya ivorensis (Mahogany), Mansonia altissima (Mansonia), Tectona grandis (Teak) were selected for the study. The densities of the woods were determined at Moisture Contents (MC) of 9.0, 12.0, and 15.0%. Selected samples from each species, were exposed to fire at temperature ranges of 20° to 230°C for 30 min; 230° to 300°C for 30 min; 20° to 300°C for 60 min. The charring rate results based on 15% moisture content for all 0 - 30 min, 30 - 60 min and 0 - 60 min, being the ones having the lowest correlation values at each of the fire exposure time were analysed using ANOVA at  and compared with selected models; Australian standard AS 1720.4 relation, Eurocode EN recommendation and White's model. At 0-30 min fire exposure (20 to 230°C), and 15% MC, the experimental charring rate results showed significant regression relations at R2 = 0.9961, 0.8586, and 0.9523 for Eurocode EN recommendation, Australian standard AS 1720.4 relation, and White's model respectively. At 0-60 min fire exposure (20 to 300°C), and 15% MC, the results of experimental charring rate also showed significant regression relations at R2 = 0.9925, 0.8926, and 0.9701 for Eurocode EN recommendation, Australian standard AS 1720.4 relation, and White's model respectively. Afara at 15.0% MC, and 20° to 300°C temperature, had the highest mean charring rates of 0.68 ± 0.02mm/min, while Opepe had the lowest charring rates of 0.47 ± 0.02 mm/min at the same MC level and temperature. The experimental test results indicated that density was a major predictor of the charring rate of constructional timber. Opepe specie, having the highest density exhibited the lowest charring rate and is recommended to ensure the safety and comfort of occupants in case of fire outbreak.